Generation Z Travel Behaviour and Changes in Travel MicroTrends - Ni Ketut Wiwiek Agustina; Made Dewinda Yudi Astari (ASEAN Journal on Hospitality and Tourism, 2022)
Travel behaviour will drive a trend in the tourism industry. Microtrends are fast-moving trends that impact destinations, hotels, attractions, and other businesses in the travel industry. Travel behaviour changes based on several factors; one of these factors is generation. These changes will occur as Gen Z travel patterns continue to evolve.  This study aims to answer the characteristics, travel behaviour, and how the travel microtrends of Gen Z in Bali shape the present and future. The research method used qualitative with an exploratory study approach. Literature reviews, observations, and interviews are used to collect data. This study found that Gen Z will prioritise health factors, both environmental and mental health in the future. The study also found that Gen Z favours sustainable accommodation.